RITUALS FOR HARMONY: EXPLORING THE BERSIH DUSUN LOCAL GENIUS BEHIND RUBBER TAPPING - Hasse J. (Al-Albab, 2014)
Differences have long been a natural marker of the dynamics of the relationship of society. Differences often become obstacles in creating social stability. Diversity can be a strength if managed properly, but may become a source of conflict in case of faulty management. This short article addresses the issue of how to manage diversity so as to produce harmony in society that has different beliefs. There are three basic things defined in this paper. First, a society is capable of being integrated through commonly shared events. Second, providing room for all of the elements of society gives rise to collective solidarity which allows differences -even conflicts-- to be turned into unity. Third, the typicality of ritual that continues to be practiced in society can be optimized to serve as the medium that manages the differences and turned them to peace.